PERAN FAKTOR KEBERSAMAAN DAN KEKELUARGAAN DALAM MENINGKATKAN PRESTASI TARUNA TARUNI DI POLITEKNIK PENERBANGAN MEDAN - Muhammad Caesar Akbar; Sukarwoto Sukarwoto; Noval Kurnia Silaen (Lafadz Jaya Publisher, 2023)
This research aims to describe the role of togetherness and family factors in improving the performance of male and female cadets at the Medan Aviation Polytechnic using a qualitative approach with a literature review method. Cadets are students undergoing education at the Medan Aviation Polytechnic to prepare themselves as professionals in the aviation industry. This research employs a qualitative approach with a literature review method involving data collection from relevant sources such as books, scientific articles, and journals related to the role of togetherness and family factors in enhancing the performance of cadets. The obtained data is analyzed through reading, synthesis, and interpretation processes to depict the roles played by these factors. The research findings indicate that togetherness and family factors play a crucial role in improving the performance of cadets at the Medan Aviation Polytechnic. Harmony in relationships among cadets, mutual trust, and support and respect for each other can create an environment conducive to the growth and development of cadets. These factors contribute to increased motivation for learning, active engagement in academic activities, and better achievement. This research provides in-depth understanding of the role of togetherness and family factors in enhancing the performance of cadets at the Medan Aviation Polytechnic. The research findings can serve as a reference for educational institutions and relevant parties in developing strategies and programs that promote togetherness and family values among cadets. By enhancing these factors, it is expected that both the academic and non-academic achievements of cadets can be significantly improved.